Indeed your dancing days are done - Arnold Gordenstein (Ilha do Desterro)
The bar also served as an hotel desk. The tall American was on the top floor, the old man told Jon, but only paying guests were permitted upstairs. He'd send up a girl to get him. Jon asked if only paying guests could take a leak and pushed the swinging doors aside and ambled down the hall.